Exploring the retention and success of students with disability in Australian higher education. Issue 7 (3rd July 2017) - Kilpatrick, S.; Johns, S.; Barnes, R.; Fischer, S.; McLennan, D.; Magnussen, K.
ABSTRACT: The proportion of higher education students with disability is increasing. We know there is institutional variation in retention and performance of higher education students with disability, and there is a need to understand the reasons for this. This exploratory national study examines supports and adjustments provided by universities, including the role of disability practitioners, influence retention and performance of students with disability. The study uses a mixed-methods approach. National equity retention and performance data are analysed by higher education institution. Qualitative data on institutional policies and practices collected from a purposive sample of Australian higher education institutions are then analysed. Findings from the study include identification of factors linked to retention and performance of students with disability, including different types of disability.